GEN AI-TPACK Workshop for Strengthening Teachers’ TPACK Competences - Eni Kurniawati; Nur Rosita; Salam Mairi; Fitrawati; Meira Anggia Putri (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
This activity aims to provide technical guidance for strengthening TPACK or Technological Pedagogical Content Knowledge using the GEN AI-TPACK Framework approach. TPACK is a 21st-century teacher knowledge framework that helps support teaching skills. Meanwhile, GEN AI-TPACK is an adaptation of teachers' abilities to the use of artificial intelligence in education. This framework introduces TK, TPK, TCL, TPCK, and XK in the model for improving teacher competence. This activity is one of the effective ways to enhance teachers' professional and pedagogical competence. In addition, this training guidance also provides the benefit of digital literacy proficiency for teachers in learning in the digital era.